Differential health reporting error among older adults in India - Anna Choi; Arnab K. Basu; Nancy H. Chau; T. V Sekher (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper studies the education gradient associated with health reporting errors for two highly prevalent non-communicable diseases among older adults in India. We leverage a novel data set-the Longitudinal Aging Study in India (2017-18) panel survey-to unpack the sources of health reporting error in a developing-country context for the first time. Our analysis points to a statistically significant level of false negative reporting (or over-reporting) for both high blood pressure and depression by those with no schooling and less than middle school education relative to their more highly educated peers. Interestingly, this result is driven by those whose income is above the poverty line. We further find false negative reporting for high blood pressure to be more prevalent among women with no schooling.
Keywords: 330; high blood pressure; depression; reporting error; education